A copper-templated, bifunctional organocatalyst: a strongly cooperative dynamic system for the aldol reaction. Issue 31 (27th July 2017) - Serra-Pont, Anna; Alfonso, Ignacio; Solà, Jordi; Jimeno, Ciril
Abstract : A copper-templated bifunctional organocatalyst delivers aldol adducts in high yields and stereoselectivities. Abstract : The study of novel metal-templated dynamic organocatalytic systems has led to the identification of CuSO4 as the most efficient template to assemble monofunctional prolinamide- and thiourea-modified pyridine ligands. The structural and electronic requirements to assemble an efficient catalyst have been disclosed: both pyridine ligands must bear a 1, 3-substitution pattern, and the thiourea ligand serves as a reducing agent to copper(i ) as well. Eventually, the cooperative effects achieved with such a simple system deliver high reaction rates and stereoselectivities at room temperature in the asymmetric aldol reaction, requiring only 1 mol% of copper salt.